Siblings of individuals with severe mental illness. Issue 4 (2nd December 2014) - Sin, Jacqueline; Spain, Debbie; Jordan, Cheryl; A. Griffiths, Christopher
Abstract : Purpose: – The importance of providing information, support and interventions for family members and carers of people who have severe mental illness (SMI) has garnered increasing attention in recent years. However, research to date has primarily focused on parents; the purpose of this paper is to review the literature investigating the experiences of siblings of individuals who have SMI. Design/methodology/approach: – A literature review was undertaken to summarise the empirical data regarding the experiences and needs of siblings, and their potential contribution to supporting their siblings' recovery journey. Findings: – Sibling views, experiences and needs have thus far been little explored. Yet siblings often make significant contributions to their brother's/sister's care and social and emotional well-being, and their support can positively shape the recovery trajectory. This review finds that siblings require information and support for two reasons: to maintain their own well-being, and to be able to best support their sibling with SMI and the family as a whole. Several implications for clinical practice, workforce development and research are outlined. Originality/value: – This paper provides a timely review of the literature to enhance awareness of the needs and experiences of siblings for health and social care professionals. Examples of good practice are proposed for statutory and voluntary service settings.